Efecto de dosis subletales de biomoléculas con potencial insecticida en Bactericera cockerelli en condiciones de laboratorio - González González, Kerly Tamara (2023)
Bactericera cockerelli (Šulc) (Hemiptera: Triozidae); represents a potential threat to tomato production Solanum lycopersicum causing direct and indirect damage; For its control several alternatives are investigated; standing out among them biomolecules of plant origin, such as essential oils. However, most of the researches evaluate the lethality of biocompounds in adults, neglecting the possible sublethal effects in adults or immature states, as well as the possible ovicidal effect. Therefore, here, the sublethal effect of two plant species Ruta graveolens and Ocotea quixos on B. cockerelli adults and nymphs was evaluated; and its possible ovicidal effect. Adults and fifth instar nymphs were exposed by contact to sublethal doses of R. graveolens (CL10= 0.59 μL/mL CL25= 0.83 μL/mL and CL50= 1.72 μL/mL) or O. quixos (CL10= 0.13 μL/mL CL25= 0.22 μL/mL and CL50= 0.40 μL/mL); similarly, B. cockerelli eggs at 24, 48, 72 or 96 hours of age were exposed to the CL95 of these two essential oils; 2.92 μL/mL and 1.67 μL/mL of R. graveolens and O. quixos respectively. Survival results on adults showed a survival inversely proportional to the exposed concentration. Similarly, the survival of B. cokerelli was reduced depending on the concentrations of O. quixos (CL10= 0.13 μL/mL CL25= 0.22 μL/mL and CL50= 0.40 μL/mL) with the exception of CL10 and CL25 where there was no significant difference between them. The R. graveolens oil (CL95= 2.92 μL/mL) did not present an ovicidal effect on B. cockerelli eggs at any of its stages, unlike the O. quixos oil (CL95= 1.67 μL/mL) that reduced the hatching of eggs at 96 h. In other words, this study shows that these oils could be used to control the population of B. cockerelli. Key words: Sublethal dose, Ovicidal effect, Tomato psyllid, Survival.